(untitled) (Itinera, 2024)
The paper intends to reflect on the function of digital technology within the field of aesthetics. Through Marina Abramović’s work The Life (2019) the aim is to rethink the relationship between the artistic object and subjective consciousness in a phenomenological key. The Serbian artist’s work uses the innovative and original technique of mixed reality; this new horizon leads to new philosophical frontiers relating to the perception of the body, experience (Erlebnis), experience and intuition. We will try to focus attention on the relationship between virtuality and reality by comparing mixed reality with purely virtual reality and augmented reality. Even the relationship with the public and the spectator is defined from a different, broader point of view in which the experience of the artistic object becomes a philosophically immersive experience. The presence-absence of the artist expresses the new aesthetic horizons supported by digital, opening up to a series of problems which, especially in the phenomenological field, mark the current debate.